Atomically modified thin interface in metal-dielectric hetero-integrated systems: control of electronic properties. (1st March 2017) - Iida, Kenji; Nobusada, Katsuyuki
Abstract: We have performed first-principles studies of the electronic properties of Cu-diamond hetero-integrated systems, particularly placing emphasis on elucidating the effects of surface modification of diamond with H or O. It is found that the electronic properties crucially depend on the chemical compositions of the modified atomically thin interface region. The local density of states (LDOS) of the H-terminated diamond moiety near the Cu surface exhibits a clearly different distribution from that near the vacuum region, whereas the LDOS of the O-terminated diamond is almost independent of the Cu deposition. In other words, the effects of the electronic interactions between Cu and diamond on the electronic properties in the interface region are readily controlled by surface modification with only one atomic (i.e. H or O) layer. Electric field (EF) effects on the Cu-diamond systems also strongly depend on the electronic details, i.e. atomistic modification in the interface regions. In particular, at the interface between the H-terminated diamond moiety and the vacuum region, its conduction band energy is strongly affected by an applied EF much more than the valence band energy; that is, the band gap can be varied with an applied EF. The band gap variation is found to be attributed to an atomistic level difference in the spatial extension of the valence and conduction bands and thus is not explained with a macroscopic band diagram model. It has been demonstrated that the electronic properties of hetero-integrated systems are described and controlled well by carefully designing atomically thin interface regions.